Age, education and gender effects on Wisconsin card sorting test: standardization, reliability and validity in healthy Argentinian adults. Issue 6 (1st November 2020) - Miranda, Agustín R.; Franchetto Sierra, Juliana; Martínez Roulet, Amparo; Rivadero, Luisina; Serra, Silvana V.; Soria, Elio A.
ABSTRACT: The Wisconsin Card Sorting Test (WCST) is a widely used neuropsychological assessment of executive functioning. The aim of this study was to provide norm values and analyze the psychometric properties of WCST in healthy Argentinian adults aged from 18 to 89 years old ( N = 235). Descriptive statistics are reported as means, standard deviations and percentiles, with the effects of age, education and gender being investigated by ANOVA, and with the effect sizes being calculated. The psychometrics were studied using the WCST structure, reliability, convergent validity, and discriminant validity, and WCST norms adjusted for age and educational level are proposed. This instrument is a reliable and valid tool for the assessment of executive functions. However, as the age- and educational-related effects were demonstrated, these characteristics need to be considered before interpreting WCST scores. Regarding gender, no differences were found. Our results expand the geographical and sociocultural applicability of WCST.